2021
DOI: 10.1128/msphere.01071-20
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Profiles Associated with Inducible Adhesion in Candida parapsilosis

Abstract: Candida parapsilosis has emerged as a frequent cause of invasive candidiasis with increasing evidence of unique biological features relative to C. albicans. As it adapts to conditions within a mammalian host, rapid changes in gene expression are necessary to facilitate colonization and persistence in this environment. Adhesion of the organism to biological surfaces is a key first step in this process and is the focus of this study. Building on previous observations showing the importance of a member of the ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Two recent studies reported on C. parapsilosis ALS gene expression using real-time PCR [49] or RNAseq analysis [50] of strains with different adhesive capacity under adhesioninducing as well as non-inducing conditions. Both studies suggest that, despite some observed upregulation of ALS7/CPAR2_404800 in one strain under adhesion-inducing conditions [50], the regulation of ALS genes depended more on phenotypic strain variability than on growth conditions. Our data concur with this view, and indicate that this is also the case for the Hwp and Hyr adhesin families.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported on C. parapsilosis ALS gene expression using real-time PCR [49] or RNAseq analysis [50] of strains with different adhesive capacity under adhesioninducing as well as non-inducing conditions. Both studies suggest that, despite some observed upregulation of ALS7/CPAR2_404800 in one strain under adhesion-inducing conditions [50], the regulation of ALS genes depended more on phenotypic strain variability than on growth conditions. Our data concur with this view, and indicate that this is also the case for the Hwp and Hyr adhesin families.…”
Section: Discussionmentioning
confidence: 99%
“…Although transcriptomic studies carried out so far suggested that the proteins encoded by the ALS genes may represent an important inducible factor in the virulence of C. parapsilosis , responsible for the adhesion of yeast to host cells and proteins (Bliss et al, 2021; Neale et al, 2018), the surface exposition of their protein products and actual involvement in interactions with host cells have only occasionally been confirmed (Karkowska‐Kuleta et al, 2017; Kozik et al, 2015). As previous reports indicated enhanced expression of genes encoding C. parapsilosis adhesins under conditions that mimic the host environment (Bliss et al, 2021), in the current studies we first verified the surface exposition of Als proteins on the fungal cell wall using LC‐MS/MS and direct tryptic hydrolysis of proteins displayed on intact fungal cells, after the growth of C. parapsilosis in DMEM or MCDB131 media, which are routinely used to cultivate cells of the epithelial cell line A431 and the endothelial cell line HMEC‐1, respectively. The data obtained confirmed the presence of both proteins—CPAR2_404800 and CPAR2_404780—on the fungal cell surface under the growth conditions used, while other proteins from this family were not identified in this study by the method applied (Supporting Information: Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, initially, our objective was to investigate the direct involvement of these two fungal proteins in the binding of human epithelial and endothelial cells. Observations from gene expression studies obtained to date only indirectly indicated the involvement of Als proteins from C. parapsilosis in interactions with host cells, considering, in particular, the complexity of the adhesion process and differentiation in fungal adhesive phenotypes (Bertini et al, 2016; Bliss et al, 2021; Zoppo, Di Luca et al, 2020; Zoppo, Fiorentini, et al, 2020). Therefore, in the current study we decided to use proteins CPAR2_404800 and CPAR2_404780 after their isolation from the cell surface and chromatographic purification, and then test their ability to interact with human cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations